Geometric map matching algorithm analysis [electronic resource] - Chan, Kong Yu, 1988- 638513 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2012